Examining Word Factors and Child Factors for Acquisition of Conditional Sound-Spelling Consistencies: A Longitudinal Study. (3rd July 2016) - Kim, Young-Suk Grace; Petscher, Yaacov; Park, Younghee
ABSTRACT: It has been suggested that children acquire spelling by picking up conditional sound-spelling consistencies. To examine this hypothesis, we investigated how variation in word characteristics (words that vary systematically in terms of phoneme-grapheme correspondences) and child factors (individual differences in the ability to extract phonological, morphological, and orthographic information) simultaneously relates to spelling accuracy. A total of 143 Korean-speaking children were assessed on spelling 4 times from prekindergarten to kindergarten. Words in the spelling task systematically varied in orthographic transparency stemming from phonological shifts. At Time 1 they were also assessed on emergent literacy or linguistic awareness skills (e.g., phonological awareness, morphological awareness, letter-name knowledge). Explanatory item response model revealed that (a) growth trajectories of spelling differed as a function of orthographic transparency, and (b) the effect of emergent literacy skills on words of varying transparency differed as a function of children's emergent literacy skill levels and time.